Association of systemic secondary brain insults and outcome in patients with convulsive status epilepticus: A post hoc study of a randomized controlled trial. (3rd November 2020) - Fontaine, Candice; Lemiale, Virginie; Resche-Rigon, Matthieu; Schenck, Maleka; Chelly, Jonathan; Geeraerts, Thomas; Hamdi, Aicha; Guitton, Christophe; Meziani, Ferhat; Lefrant, Jean-Yves; Megarbane, Bruno; Mentec, Hervé; et al.
Abstract : Objective: To evaluate the association between systemic factors (mean arterial blood pressure, arterial partial pressures of carbon dioxide and oxygen, body temperature, natremia, and glycemia) on day 1 and neurologic outcomes 90 days after convulsive status epilepticus. Methods: This was a post hoc analysis of the Evaluation of Therapeutic Hypothermia in Convulsive Status Epilepticus in Adults in Intensive Care (HYBERNATUS) multicenter open-label controlled trial, which randomized 270 critically ill patients with convulsive status epilepticus requiring mechanical ventilation to therapeutic hypothermia (32°C–34°C for 24 hours) plus standard care or standard care alone between March 2011 and January 2015. The primary endpoint was a Glasgow Outcome Scale score of 5, defining a favorable outcome, 90 days after convulsive status epilepticus. Results: The 172 men and 93 women had a median age of 57 years (45–68 years). Among them, 130 (49%) had a history of epilepsy, and 59 (29%) had a primary brain insult. Convulsive status epilepticus was refractory in 86 (32%) patients, and total seizure duration was 67 minutes (35–120 minutes). The 90-day outcome was unfavorable in 126 (48%) patients. In multivariate analysis, none of the systemic secondary brain insults were associated with outcome; achieving an unfavorable outcome was associated with age >65 years (odds ratio [OR] 2.17, 95% confidence interval [CI] 1.20–3.85; p = 0.01), refractory convulsive status epilepticus (OR 2.00, 95% CI 1.04–3.85; p = 0.04), primary brain insult (OR 2.00, 95% CI 1.02–4.00; p = 0.047), and no bystander-witnessed seizure onset (OR 2.49, 95% CI 1.05–5.59; p = 0.04). Conclusions: In our population, systemic secondary brain insults were not associated with outcome in critically ill patients with convulsive status epilepticus. ClinicalTrials.gov identifier: NCT01359332.